Forecasting return products in an integrated forward/reverse supply chain utilizing an ANFIS - Kumar, D. Thresh; Soleimani, Hamed; Kannan, Govindan (Zielona Góra: Uniwersytet Zielonogórski)
Interests in Closed-Loop Supply Chain (CLSC) issues are growing day by day within the academia, companies, and customers. Many papers discuss profitability or cost reduction impacts of remanufacturing, but a very important point is almost missing. Indeed, there is no guarantee about the amounts of return products even if we know a lot about demands of first products. This uncertainty is due to reasons such as companies` capabilities in collecting End-of-Life (EOL) products, customers` interests in returning (and current incentives), and other independent collectors.
Keywords: artificial neural networks; adaptive network based fuzzy inference system; closed-loop supply chain; forecasting methods; fuzzy neural network